Military-Patriotic Education Under Martial Law: Challenges for Ukrainian Education - Skirda, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article highlights the key factors to consider when implementing the educational process and organizing military-patriotic education. It analyzes the scientific discourse on the organization and realization of military-patriotic education in Ukraine. It identifies the main challenges faced by educational institutions under martial law (security, psychological, organizational, adaptive, resourcerelated, and digital). It is determined that the challenges for Ukrainian education under martial law, which have influenced the content, forms, and conditions of organizing military-patriotic education, include the following: violation of the basic security function of education due to targeted shelling of schools, bombardment of civilian infrastructure, and destruction; massive internal displacement of the population, which created uneven distribution of human resources and deepened the differentiation of educational opportunities; significant differences in the experiences of learners, requiring education to be based on individualization and flexible responses to diverse life contexts of participants in the educational process; an increased level of psychological vulnerability among children and teachers in crisis conditions, necessitating the provision of psychological safety and systemic emotional support as a key component in organizing military-patriotic education; and the spread of digital content accompanied by the risks of disinformation, propaganda, and distortion of reality. The practical focus of military-patriotic education is revealed, including life safety, survival basics under combat conditions, first aid training, and game-based and modelling practices with elements of evacuation, reconnaissance, and land navigation. It is substantiated that in the new realities, the implementation of military-patriotic education requires flexibility and integration into the educational process, combining instruction with systematic educational work while ensuring educational continuity, adapting to blended learning formats, and creating a safe environment.